Perbedaan Kadar Glukosa Darah Sewaktu Pada Penderita St Elevasi Miokard Infark (Stemi) Dan Non-St Elevasi Miokard Infark (Nstemi) Di Rsud Dr. Moewardi - Priscillah, Wildan; , Dr. Iin Novita Nurhidayati Mahmuda, M.Sc, Sp.PD (2017)
Background : Coronary Heart Disease (CHD) is cardiac dysfunction caused by restricted blood supply in myocardium. There is blockage or narrowing of the coronary arteries. Stres hyperglicemia is associated with metabolic response to stres or injury (trauma). there are complex interaction that involving several mediators, including neurology, hormone and cytokine messenger Objective : The aim of this study is to determine the differences between blood glucose level in patient with ST elevation myocardial infarction (STEMI) and Non-ST elevation myocardial infartion (NSTEMI) Methods : An observational study with cross sectional approach. Sample was taken by purposive sampling technique. Total sample are 70 people, 35 people with STEMI and 35 people with NTSTEMI. Data collected by using medical records of patient and it is analyzed by unpaired T Test. Results: Blood glucose level of 172.49 mg/dl in patient with STEMI and 128.86 mg/dl in NSTEMI. By the significancy value 0,000 (p < 0.05). Conclusion : There are differences between blood glucose level in patient with ST elevation myocardial infarction (STEMI) and Non-ST elevation myocardial infartion (NSTEMI). Blood glucose level in patient with STEMI is higher than NSTEMI.